Conducta obstétrica en multípara de 40 años de edad y 35 semanas de gestación con placenta previa. - Torres Muñoz, Madyson Yezabell (2021)
Placenta previa is the insertion of the placenta in the lower segment of the uterus, as this pathology is linked to various maternal and ovular factors, as well as being one of the main causes of bleeding in the second and third trimesters of pregnancy, increasing the rates of cessation since on many occasions this pathology makes it impossible for women to have a normal delivery. The objective of this clinical case is to identify the maternal and fetal complications of placenta previa in a 35-week pregnancy. This observational, clinical and descriptive study was carried out in a period of three days in 2020 on a patient with a complicated placenta previa with placental abruption at the Hospital Sagrado Corazón de Jesús, which was captured in the obstetric-gynecological emergency and her diagnosis was corroborated by the specialist on duty. Of all the patients who come to this health home every day, 1 out of every 30 gynecological-obstetric patients turn out to have a diagnosis with placenta previa, some asymptomatic and others symptomatic, thus each having their own management. A good anamnesis and the identification of risk factors together with an abdominal ultrasound helps us to be able to confirm a placenta previa and thus be able to avoid some complications associated with this pathology that put the life of the mother at risk, such as that of the fetus.